Penerapan Teori Kecerdasan Majemuk melalui Model Pembelajaran Inklusif untuk Meningkatkan Pemahaman Siswa Slow Learner di Kelas VI Sekolah Dasar - Fatimah, Nining (Lentera: Jurnal Ilmiah Kependidikan, 2024)
This research aims to improve the understanding of slow learner students in grade 6 in Natural and Social Sciences (IPAS) subjects by applying the theory of multiple intelligences through an inclusive learning model. The focus of this research material is on continents. Slow learner students have difficulty reading, so their learning goals are different from non-slow learner students. Non-slow learner students are expected to be able to understand and detail the six continents, while slow learner students are expected to be able to read and write the names of the six continents. This research uses qualitative methods with data collection techniques in the form of observation, interviews and documentation. Data analysis was carried out inductively to find patterns and themes that emerged from the field data. The research results show that the theory of applying multiple intelligences and inclusive learning models is able to improve the basic literacy skills of slow learner students and provide meaningful learning experiences for non-slow learner students. Apart from that, inclusive learning that is tailored to individual needs can increase the learning motivation of slow learner students. The conclusion of this research is that a learning approach that combines the theory of multiple intelligences and an inclusive model is effective in increasing the understanding of students with special needs. It is recommended that teachers continue to develop learning strategies that suit students' learning styles and carry out ongoing evaluations to maximize the potential of each student.